Correlation study on Arabic Placement Test (APT) levels and SPM results for 2019/2020 new intake students - Arshad, Mastura; Samat, Nur Arifah; Mustapai, Mohd Zulhisyam; Ab Jabbar, Muhammad Bahari; Abdul Latif, Nadhirah; Mohd Zaki, Mohd Zul Amin (Centre For Foundation Studies (CFS), 2021)
This study is an alternative plan for temporary replacement of Arabic Placement Test (APT) that could not be implemented during the Movement Control Order (MCO) in the year 2020 due to Covid-19 pandemic. The APT is an instrument used to identify students’ proficiency levels in Arabic language and to place them into Quranic Language levels accordingly. This study involves year 2019/2020 new intake students’ data. The aim of this study is to place 2020/2021 new intake students into Quranic language courses according to their Arabic in SPM results in line with the previous 2019/2020 new intake students’ data. The data is analyzed using Chi-Square test to measure the association between APT levels and Arabic in SPM results. This study is only an alternative plan for temporary placement of APT and it can never be as good as the original. However, this study offers a good solution to the placement issues which arise due to Covid-19 pandemic.